Pola Tradisi Minum Jamu: Upaya Pemertahanan Pengobatan Lokal Sebagai Identitas Masyarakat Bangkalan Madura - Ekna Satriyati (DIMENSI - Journal of Sociology, 2016)
Herbal drink in the local tradition Bangkalan Madura is a manifestation of culture in responding to and resolving the health problems experienced daily. The tradition of drinking and making herbal medicine has become part of a culturethat is agreed upon by the community. In the development of the tradition of herbal drink to change the meaning in its implementation. Young people are not completely leaving but did not do a whole tradition of herbal drink. Thephenomenon of lax implementation of the traditions of herbal drink made gatherers and the elderly maintain the effort to pass through various stages of life in the tradition obligations. The study aimed to describe patterns and usergatherers efforts in maintaining the tradition of herbal medicine herbal drink. The location in the town of Bangkalan Madura by collecting data through participant observation and interviews with 30 informants (15-gatherers and 15users of herbal medicine). Data were analyzed using descriptive qualitative. The study found that the patterns of the efforts made gatherers and users in maintaining the tradition of herbal medicine: First, efforts to implement theappropriate understanding of tradition. Second, effective communication efforts among actors tradition. Third, efforts to introduce herbal medicine as Madura community identity during migration.